Home Garden With Eco-Healing Functions Benefiting Mental Health and Biodiversity During and After the COVID-19 Pandemic: A Scoping Review - Xindi Zhang (Frontiers Media S.A., 2021)
The COVID-19 pandemic has led to tremendous impacts on human lives and society, which are not only because of negative effects on people's mental health due to isolation policies and physical distance for mitigating the spread of SARS-CoV-2, but also because the incident post-acute sequelae of the coronavirus will cause mental disorders. A green environment is a health resource, which cannot only benefit human physical and mental health, but also increases biodiversity, contributes to flood mitigation, and cools urban areas. A home garden, as a kind of small green space, can provide ecosystem services with eco-healing functions in reducing mental stress during the isolation period of the COVID-19 pandemic through the garden itself and physical activities in it. Such an eco-healing approach within a mini-therapeutic landscape can also benefit biodiversity by enhancing plant diversity in residence and increasing biodiversity at a large scale. In this article, we propose a conceptual framework describing a home garden as “ecological medicine” with healing functions to improve mental health, as well as indirectly enhancing urban biodiversity. A home garden, as a mini-type of green landscape with biodiversity content, allows people to get close with nature so that it can promote comfortable and natural feelings during the pandemic. Furthermore, such an eco-healing home garden approach benefiting urban biodiversity can meet the challenges in maintaining environmental and mental health in post COVID-19 pandemic recovery, as well as preparing unknown next-surge risks with potential isolation regulations.